The Number of Vaginal Epithellial and Neutrophil Strongly Correlates with the Occurrence of Premature Delivery - Sandra, Alia (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To investigate the relationship of the amount of vagina epithelia and neutrophil with premature delivery. The study was carried out in several hospitals at Obstetrics and Gynecology Department of the Faculty of Medicine Hasanuddin University, from September 2011 to January 2012. Methods: The study was cross-sectional study involving two groups of sample: premature delivery group fulfilling inclusive criteria and a control group of normal delivery. The total samples are 48 persons, comprising of 16 premature deliveries, and 32 normal pregnancy. Result: The study revealed that there was a significant correlation between ≥1 parity and premature delivery (p